Symptoms of bipolar disorder are associated with lower bariatric surgery completion rates and higher food addiction. (January 2021) - Holgerson, Allison A.; Clark, Matthew M.; Frye, Mark A.; Kellogg, Todd A.; Mundi, Manpreet S.; Veldic, Marin; Grothe, Karen
Abstract: Background: Bipolar disorder (BP) is highly comorbid with obesity, however, little is known about how BP might be associated with bariatric surgery outcomes. Methods: In this retrospective clinical cohort study, 1034 patients completed a psychological evaluation, and screening positive for possible BP was defined as a score ≥7 and moderate disability on the Mood Disorders Questionnaire. Food addiction (FA), subthreshold binge eating disorder (BED), and illegal drug use were also assessed using standardized questionnaires. Results: The 54 (5.2%) patients screening positive for BP were less likely to have bariatric surgery compared to 980 (94.8%) patients who screened negative for BP (5 patients or 9.3% vs 273 patients, or 27.9%). Patients with possible BP also had significantly higher prevalence of FA (37% vs 13.2%), subthreshold BED (29.6% vs 8.3%) and illegal drug use (7.4% vs 2.1%). Conclusions: In this retrospective clinical cohort study, patients who screened positive for BP had a higher prevalence of food addiction, subthreshold binge eating disorder and recent illegal drug use. They also demonstrated lower completion rates for having bariatric surgery. Clearly, more needs to be learned about how to help patients with symptoms of bipolar disorder manage their obesity and behavioral challenges. Highlights: Prevalence of bipolar disorder in patients seeking bariatric surgery appears to be higher than in the general population. Patients with bipolar disorder have low rates of completing bariatric surgery. In patients seeking bariatric surgery, bipolar disorder is associated with food addiction.